Tahun 2007-2009 ANALISIS STRUKTUR, KONSENTRASI DAN EFISIENSI PASAR INDUSTRI OTOMOTIF DAN PRODUK OTOMOTIF DI INDONESIA TAHUN 2007-2009 - Piet Aprilianus (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2010)
The purpose of this study is to analyze market structure and efficiency of Automotive Industry in Indonesia periode 2007-2009 market structure is measured by using concentration Ratio and efficiency of the Industry is measured by using Data Enrespment Analysis. The result of this study show that market several of Automotive Industry in Indonesia oligopoly the competition level of Automotive Industry is concentrated and foor automotive company with biggest to me asset here 100% efficiency level for there years. The companies are PT. Astra International, PT. United Tractors, PT. Indomobil Sukses Internasional and PT. Astra Otoparts. While one company that did not had 100% efficiency level from 2007 untuil 2009 is Pt. Gajah Tunggal in addition, can be know that dominanct factor causing the efficiency of PT. Gajah Tunggal is input of capital.Keywords: Structure Concentration And Efficiency, Indonesia Automotive Industry